Analisis Kemampuan Representasi Matematis Siswa SMP dalam Menyelesaikan Soal Sistem Persamaan Linear Dua Variabel - Yuhanni, Anni; Zayyadi, Moh; Aini, Septi Dariyatul (Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to describe the mathematical representation ability of eighth-grade junior high school students in solving Two-Variable Linear Equation Systems (SLS). The method used is descriptive qualitative with 30 students selected through purposive sampling as subjects. The research instrument is a mathematical representation ability test consisting of three SLS questions and interviews. The results of the study indicate that students' mathematical representation abilities are divided into high, medium, and low categories. High category students are able to fulfill symbolic and visual representations, but are still weak in verbal representations. Medium category students are quite good in symbolic representations, but still experience errors in visual and verbal representations. Meanwhile, low category students experience difficulties in all representation indicators. These findings indicate that students' mathematical representation abilities in SLS material are not optimal and require more effective learning strategies.